2014
DOI: 10.1007/s00705-014-2024-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of Toll-like receptor agonist adjuvants on the efficiency of a DNA vaccine

Abstract: We have investigated whether poly(I:C) Toll-like receptor 3 (TLR3) and resiquimod Toll-like receptor 7 (TLR7) agonists can serve as vaccine adjuvants and promote the efficiency of therapeutic DNA vaccination against tumors expressing the human papilloma virus 16 (HPV-16) E7 protein. For this purpose, C57BL/6 mice were inoculated with 2 × 10(5) TC-1 cells, and they were then immunized with HPV-16 E7 DNA vaccine alone or with 50 μg of resiquimod or poly(I:C) individually. We found that poly(I:C) and resiquimod c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…Therefore, activation of TLRs promotes both innate inflammatory responses and the induction of adaptive immunity. Stimulating TLR signaling during DNA vaccination can enhance the induction of vaccine-specific responses (Gableh et al, 2016; Pavlenko et al, 2007; Sajadian et al, 2014). As described above, plasmid DNA vaccines naturally stimulate TLR9, which interacts with unmethylated CpG DNA from bacteria, some viruses and plasmid DNA.…”
Section: Dna Vaccines – Adjuvants and Prime-boost Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, activation of TLRs promotes both innate inflammatory responses and the induction of adaptive immunity. Stimulating TLR signaling during DNA vaccination can enhance the induction of vaccine-specific responses (Gableh et al, 2016; Pavlenko et al, 2007; Sajadian et al, 2014). As described above, plasmid DNA vaccines naturally stimulate TLR9, which interacts with unmethylated CpG DNA from bacteria, some viruses and plasmid DNA.…”
Section: Dna Vaccines – Adjuvants and Prime-boost Vaccinationmentioning
confidence: 99%
“…Sajadian and colleagues also demonstrated that the use of either TLR3 and/or TLR7 agonists in combination with a DNA vaccine encoding the HPV E7 antigen enhanced the anti-tumor capabilities of the vaccine to eliminate HPV-induced tumors in mice. Specifically, they showed that DNA vaccine alone resulted in no significant inhibitory effects on TC-1 cells in C57BL/6 mice, but the addition of poly (I:C) (TLR3 agonist) or resiquimod (TLR7 agonist) resulted in significant tumor regression (Sajadian et al, 2014). More recently, Gableh and colleagues found that stimulation of TLR4 with monophophoryl lipid A (MPL) significantly increased lymphocyte proliferation, CTL activity, IFN-γ, IL-4 and IL-12 responses, and tumor protection against TC-1 cells (Gableh et al, 2016).…”
Section: Dna Vaccines – Adjuvants and Prime-boost Vaccinationmentioning
confidence: 99%
“…Adjuvanting a DNA vaccine with the TLR9 agonist, CpG oligodeoxinucleotides (ODN), at the time of priming enhanced CD8 + T cell responses and control of viral load after SIV challenge in rhesus macaques [88]. A recent study showed that the TLR3 agonist poly (I:C) and the TLR7 agonist resiquimod were both able to induce significant tumor regression when administered together with a DNA vaccine against a model tumor expressing the HPV-16 in mice [89]. However, when a SIV DNA vaccine was administered together with poly (ICLC), a stabilized poly (I:C) analogue, in rhesus macaques, no improvement in immunogenicity was observed [90].…”
Section: Adjuvantsmentioning
confidence: 99%
“…However, despite their high immunogenicity in murine models, DNA vaccines have shown poor efficacy in large animal models and humans 2 . New strategies to improve DNA vaccines include the optimization of transcriptional control elements and codons 35 , the use of adjuvants, such as Toll-like receptor (TLR) ligands 6 , cytokine expressing plasmids 7–9 or apoptosis-based adjuvants 1012 and the choice of an appropriate delivery system such as local electroporation (EP) 1315 .…”
Section: Introductionmentioning
confidence: 99%